Answers of x

5 x + 2 x + 3 = 4 x + 1 + 3 x + 2 \frac{5}{x}+\frac{2}{x+3}=\frac{4}{x+1}+\frac{3}{x+2}

Find the sum of all real roots of x x in this quadratic equation.


The answer is -6.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

5 x + 2 x + 3 = 4 x + 1 + 3 x + 2 \frac{5}{x}+\frac{2}{x+3}=\frac{4}{x+1}+\frac{3}{x+2}

( 5 x + 1 ) + ( 2 x + 3 + 1 ) = ( 4 x + 1 + 1 ) + ( 3 x + 2 + 1 ) \left( \frac{5}{x} +1 \right) +\left(\frac{2}{x+3} +1 \right) = \left( \frac{4}{x+1}+1 \right) +\left(\frac{3}{x+2}+1 \right)

5 + x x + 5 + x x + 3 = 5 + x x + 1 + 5 + x x + 2 \frac{5+x}{x}+\frac{5+x}{x+3}=\frac{5+x}{x+1}+\frac{5+x}{x+2}

( 5 + x ) ( 1 x + 1 x + 3 1 x + 1 1 x + 2 ) = 0 (5+x)\left(\frac{1}{x}+\frac{1}{x+3}-\frac{1}{x+1}-\frac{1}{x+2}\right)=0

5 + x = 0 \Rightarrow 5+x =0 or 1 x + 1 x + 3 1 x + 1 1 x + 2 = 0 \displaystyle\frac{1}{x}+\frac{1}{x+3}-\frac{1}{x+1}-\frac{1}{x+2}=0

1 s t 1^{st} term

5 + x = 0 x = 5 5+x=0 \Rightarrow x=\boxed{-5}

2 n d 2^{nd} term

1 x + 1 x + 3 1 x + 1 1 x + 2 = 0 \frac{1}{x}+\frac{1}{x+3}-\frac{1}{x+1}-\frac{1}{x+2}=0

2 x + 3 x ( x + 3 ) = 2 x + 3 ( x + 1 ) ( x + 2 ) \frac{2x+3}{x(x+3)}=\frac{2x+3}{(x+1)(x+2)}

( 2 x + 3 ) ( 1 x 2 + 3 x 1 x 2 + 3 x + 2 ) = 0 (2x+3) \left(\frac{1}{x^2+3x}-\frac{1}{x^2+3x+2}\right)=0

2 x + 3 = 0 x = 3 2 \Rightarrow 2x+3=0 \Rightarrow x=\boxed{-\frac{3}{2}} or 1 x 2 + 3 x 1 x 2 + 3 x + 2 = 0 \displaystyle \frac{1}{x^2+3x}-\frac{1}{x^2+3x+2}=0

  • 1 x 2 + 3 x 1 x 2 + 3 x + 2 = 0 \displaystyle \frac{1}{x^2+3x}-\frac{1}{x^2+3x+2}=0 has no real roots for it.

Therefore, the sum of all real roots are 5 + ( 3 2 ) = 6.5 -5+\left(-\frac{3}{2}\right)= \boxed{-6.5}

Ikkyu San
Aug 26, 2015

5 x + 2 x + 3 = 4 x + 1 + 3 x + 2 5 ( x + 3 ) + 2 x x ( x + 3 ) = 4 ( x + 2 ) + 3 ( x + 1 ) ( x + 1 ) ( x + 2 ) 5 x + 15 + 2 x x 2 + 3 x = 4 x + 8 + 3 x + 3 x 2 + 3 x + 2 7 x + 15 x 2 + 3 x = 7 x + 11 x 2 + 3 x + 2 ( 7 x + 15 ) ( x 2 + 3 x + 2 ) = ( 7 x + 11 ) ( x 2 + 3 x ) 7 x 3 + 36 x 2 + 59 x + 30 = 7 x 3 + 32 x 2 + 33 x 4 x 2 + 26 x + 30 = 0 2 x 2 + 13 x + 15 = 0 ( 2 x + 3 ) ( x + 5 ) = 0 x = 3 2 , 5 \begin{aligned}\dfrac5x+\dfrac2{x+3}=&\ \dfrac4{x+1}+\dfrac3{x+2}\\\dfrac{5(x+3)+2x}{x(x+3)}=&\ \dfrac{4(x+2)+3(x+1)}{(x+1)(x+2)}\\\dfrac{5x+15+2x}{x^2+3x}=&\ \dfrac{4x+8+3x+3}{x^2+3x+2}\\\dfrac{7x+15}{x^2+3x}=&\ \dfrac{7x+11}{x^2+3x+2}\\(7x+15)(x^2+3x+2)=&\ (7x+11)(x^2+3x)\\7x^3+36x^2+59x+30=&\ 7x^3+32x^2+33x\\4x^2+26x+30=&\ 0\\2x^2+13x+15=&\ 0\\(2x+3)(x+5)=&\ 0\\x=&\ -\dfrac32,-5\end{aligned}

Thus, sum of all roots in above equation is ( 3 2 ) + ( 5 ) = 13 2 = 6.5 \left(-\dfrac32\right)+(-5)=-\dfrac{13}2=\boxed{6.5}

Oli Hohman
Sep 27, 2015

If you find a common denominator for both sides of the equation, you're left with

(7x+15)/(x*(x+3)) = (7x+11)/((x+1)(x+2)) Cross multiplying: 7x^3 +32x^2+33x=7x^3+36x^2+59x+30 32x^2 +33x = 36x^2+59x+30 4x^2+26x+30=0 Quadratic formula : = (-26+/- sqrt(26^2-4(4)(30))/(2(4)) (-26 +/- sqrt(676-480))/(8) (-26 +/- 14)/(8) (-13+/- 7)/4 There are only two solutions to a quadratic ---> x = -3/2, -5

-10/2 - 3/2 = -13/2 = -6.5

Neeraj Kamal
Sep 13, 2015

From solving above equation we get, 4x^2 + 26x + 30 = 0 so by applying vieta's formula we get sum of all real roots of this equation, i.e. -26/4 = -6.5

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...